Characterization and anti-tumor activity of a polysaccharide isolated from Dendrobium officinale grown in the Huoshan County - Yuan Wei; Linwei Wang; Dujun Wang; Dan Wang; Chongwei Wen; Bangxin Han; Zhen Ouyang (BMC, 2018)
Abstract Background Polysaccharides are carbohydrate chains composed of linked monosaccharide units. Accumulating studies report that polysaccharides isolated from Dendrobium officinale have a variety of functions. However, the composition and anti-tumor activity of D. officinale grown in the Huoshan area are largely unknown. Methods A polysaccharide (DOPA-1) was isolated from D. officinale by hot water extraction and ethanol precipitation, followed by purification via DEAE-cellulose and Sephadex G-100 chromatography. DOPA-1 was analyzed by infrared and nuclear magnetic resonance and then characterized by periodate oxidation and Smith degradation. The anti-tumor activity of DOPA-1 was then tested in HepG-2 cells. Results Our results show that DOPA-1 is mainly comprised of mannose, glucose, and galactose at a molar ratio of 1:0.42:0.27 and has an average molecular weight of 2.29 × 105 Da. Additionally, DOPA-1 inhibited HepG-2 cell growth in a dose-dependent manner. DOPA-1-treated HepG-2 cells also had increased reactive oxygen species (ROS) levels and decreased mitochondrial membrane potential. Furthermore, apoptosis was observed in DOPA-1-treated HepG-2 cells along with Bcl-2 downregulation and Bax upregulation at the protein level. Conclusions Our findings suggest that DOPA-1 induces apoptosis in tumor cells via altered mitochondrial function, ROS production, and altered apoptosis-related protein expression. This bioactive polysaccharide could, therefore, potentially be further developed as an anti-tumor adjuvant drug.